Quantitative easing of Fed and dollar indebtedness of emerging economies - Orémus, Ádám; Brůna, Karel, 1973-; Pour, Jiří; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2021)
The diploma thesis discusses the effect of unconventional monetary policy deployed by the Federal Reserve System after the Global Financial Crisis in 2008 on the dollar indebtedness of Brazil, India, Indonesia, South Africa, and Turkey. The first part describes the quantitative easing of the Fed and its transmission mechanism. The second part theoretically analyzes the indebtedness of emerging economies with emphasis on its origin, sustainability, and impact on the balance of payments and investment position of the country. The final part of the thesis with the method of deduction examines the effect of quantitative easing on dollar debt, capital flow, current account, exchange rate, foreign direct and portfolio investments of Fragile Five economies.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses